ECONOMIC DEVELOPMENT PARADIGM IN IBNU KHALDUN'S ECONOMIC MODEL: SYSTEMATIC LITERATUR REVIEW - Zulfikar, Zulfikar; Nawawi, Zuhrinal M.; Harahap, Isnaini (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
: The economic development paradigm in Ibn Khaldun's economic development model is based on the interdependence of economic and political variables. The model emphasizes the importance of justice and development in maintaining the stability and prosperity of a country. The aim of this systematic literature review (SLR) is to analyze how Ibn Khaldun's economic development model relates to the Preferred Reporting Items for the Systematic Review method. Data was obtained from online databases, namely Crossref, Google Scholar, Semantic Scholar, and Scopus (2018-2023), and 19 articles were obtained that were relevant to the research. By using the keyword search